2013
DOI: 10.1038/bjc.2013.396
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin-3 is overexpressed in prostate cancer and promotes cancer cell survival by protecting cells from oxidative stress

Abstract: Objective:We have previously identified peroxiredoxin-3 (PRDX-3) as a cell-surface protein that is androgen regulated in the LNCaP prostate cancer (PCa) cell line. PRDX-3 is a member of the peroxiredoxin family that are responsible for neutralising reactive oxygen species.Experimental design:PRDX-3 expression was examined in tissue from 32 patients using immunohistochemistry. Subcellular distribution was determined using confocal microscopy. PRDX-3 expression was determined in antiandrogen-resistant cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 82 publications
(101 reference statements)
1
78
0
Order By: Relevance
“…PRDX5 is also able to use cytosolic and mitochondrial thioredoxins as physiological electron donors (30). These proteins are overexpressed in several types of malignancy, including breast cancer, mesothelioma, lung cancer, cervical cancer, prostate cancer, and multiple myeloma (31). Mitochondria in cancer cells are known to contain high levels of PRDX3 and PRDX5 (32)(33)(34)(35)(36), and Song et al (37) reported that the mitochondrial PRDX3 antioxidant system, which is exclusively present in mitochondria, may be a potential target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…PRDX5 is also able to use cytosolic and mitochondrial thioredoxins as physiological electron donors (30). These proteins are overexpressed in several types of malignancy, including breast cancer, mesothelioma, lung cancer, cervical cancer, prostate cancer, and multiple myeloma (31). Mitochondria in cancer cells are known to contain high levels of PRDX3 and PRDX5 (32)(33)(34)(35)(36), and Song et al (37) reported that the mitochondrial PRDX3 antioxidant system, which is exclusively present in mitochondria, may be a potential target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since most of chemotherapy for cancers is through increase in ROS level and apoptotic induction of cancer cells (Srinivas et al 2004;Alexandre et al 2006;Singh et al 2007;Brown et al 2010), some researchers have suggested PRX3 to be a potential target for cancer therapy on the basis of above fact Song et al 2011). Although the overlapping peroxidatic activities of PRXs contributed to drug resistance of cancer cells (Kalinina et al 2012), PRX3 played an indispensable role in apoptotic regulation (Chua et al 2010;Li et al 2013b;Whitaker et al 2013;Wang et al 2014;McDonald et al 2014). Therefore, we have reason to look forward to the desired effects by suppressing the expression of PRX3.…”
Section: Discussionmentioning
confidence: 99%
“…As an active responder to oxidative stress, PRX3 (or together with PRX5, another mitochondrial PRX gene) was significantly up-regulated in most common malignancies including breast cancer (Noh et al 2001;Karihtala et al 2003;Chua et al 2010), hepatocellular carcinoma (Choi et al 2002;Qiao et al 2012), malignant mesothelioma (MM) (Kinnula et al 2002), lung cancer Park et al 2006), cervical cancer (Kim et al 2009;Hu et al 2013), colorectal neoplasm (Wu et al 2010), prostate cancer (Basu et al 2011;Whitaker et al 2013), and endometrial cancer .…”
Section: The Expression Of Prx3 and Its Involvement In Apoptosis Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…One such mechanism that radiation therapy and chemotherapy are dependent on, is the increase in intracellular ROS, thereby causing oxidative stress and eventually triggering the onset of apoptosis. 37 However, expression of PRX proteins has been observed to be elevated in various carcinomas, 35,38 suggesting that excess PRXs function to overcome the increased ROS, thus enabling cancer cells to overcome elevated oxidative stress, thereby enhancing survival. Elevated level of PRX II was found to confer radiation resistance in cancers of the head and neck region 39 and breast cancer.…”
Section: 33-35mentioning
confidence: 99%